Bat boy the complete Weekly World News comic strips - Bagge, Peter 1957- (Idea & Design Works, 2011)
Presents a compilation of the Bat Boy comic strip, including his unlikely stint as President of the United States, turbulent love affair with Treasury Secretary Beyoncé, and how he went from hero to bum in Freaktown
Keywords: Bagge, Peter -- 1957-; Comics (Graphic works); Underground comics; Bat Boy (Fictitious character) -- Comic books, strips, etc; Comic